The Role of Social Media as a Medium of Democracy in Indonesia - Ilham, Ilham; Pawane, Ahmad Rizali (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
The role of social media, which at first was merely a platform for self-existence and personal expression, has now evolved significantly into a powerful instrument capable of influencing the political dynamics and democratic climate of a country. In the current digital era, the use of social media is no longer limited to social interaction but has transformed into a strategic tool that can shape public opinion, mobilize political support, and facilitate civic engagement. This research seeks to describe how democracy adapts and thrives within this digital environment by highlighting the contribution of social media as an enabler of the democratic process. The study employs a qualitative approach using the literature review method to explore relevant theories and empirical findings concerning the intersection between social media and democracy. The findings reveal that social media platforms provide a vast space for communication, interaction, and dissemination of information among users, making it easier for individuals, groups, or political actors to build networks, share political views, and rally support across geographical and social boundaries. Social media has emerged as an alternative and complementary channel for political participation, which strengthens democratic practices and holds the potential to enhance the overall quality of democracy by making political processes more inclusive, transparent, and responsive. Furthermore, the interactive and open nature of social media empowers citizens to monitor, control, and criticize the performance of the government and public officials in real time.